Inhibitory Activity of Fermented Milk Multi Strain Lactic Acid Bacteria Against Staphylococcus Aureus ATCC 25923 - Ambarini Indah; Noor Erma Nasution; Achmad Toto Poernomo; Isnaesi Isnaeni (Universitas Airlangga, 2020)
The aim of the study was to investigate inhibitory activity of fermented milk multi strain lactic acid bacteria (LAB): Lactobacillus casei Shirota, Lactobacillus acidophilus, and Lactobacillus bulgaricus against Staphylococcus aureus ATCC 29523 at variable concentration milk using diffusion method. The multi strain culture of LAB were inoculated on skimmed and diary cow milk (DCM) at concentration of 50% and 100%; in which carbon, amino acid, fat and water concentration were different. Effect of the milk and its concentration on the inhibitory activity against the test bacteria was observed as well as decreasing milk acidity and increasing of milk viscosity after 24 hours incubation. Results showed that the performance of LAB in two kinds of milks at 50% and 100% concentrations were different. On the lower milk concentration, the acidity was lower than on the 100% milk, while on the higher milk concentration, the viscosity was bigger than on the 50% concentration. The fermented milk of L. cassei Sirota did not show inhibitory activity. The multi strain of LAB on the DCM at concentration of 50% and 100% showed antibacterial activity againts Staphylococcus aureus ATCC 25923, while the skimmedmed milk fermentation showed lower inhibitory activity on both concentrations.